Employment Creation and Poverty Reduction in Nigeria: A Case of Farmers’ Cooperative Societies in Kano State, Nigeria. - Mohammed, Murtala; Mugerwa, Eric B. (NIU Journal of Humanities, 2017)
This study examines the role of employment creation on poverty reduction among members of farmers’ cooperative societies in Kano State Nigeria. A cross-sectional survey research design was adopted. Primary data collection method was used in which self-administered questionnaire were distributed to a total sample of 217 respondents selected from the target population of 498 members of farmers’ multi-purpose cooperative societies. Pearson correlation and binary logistic regression model were used to determine the influence of employment creation on poverty reduction among the respondents. The mean per capita expenditure was used as a dependent variable, while employment creation as the independent variable. The findings indicated that female were more affected by poverty than their male counterparts. Gender was not a significant factor that determined poverty level in this research. Young and middle age were the majority of the respondents and these age groups were more affected by poverty. Age was found as a significant factor that determined poverty level in this research. Majority of the respondents had household size of 7 to above 12, and the respondents with large family size were more affected by poverty than those with small ones. The household size was found as a significant factor that determined poverty level in this research. Majority of the respondents had low educational qualifications, and the respondents with low educational qualifications were more affected by poverty than those with higher educational qualifications. The educational qualification was found as a significant factor that determined poverty level in this research. The results further showed that employment was found as statistically significant factors that contributed towards poverty reduction among members of farmers’ cooperative societies in this study, and the study recommended that age, family size, educational qualifications, and given adequate soft loans should be considered when designing employment creation programmes for poverty reduction.   Key Words: Employment Creation, poverty, Farmers’ cooperative societies.